Construction of p-n heterojunction -Bi2O3/BiVO4 nanocomposite with improved photoinduced charge transfer property and enhanced activity in degradation of ortho-dichlorobenzene - Sun, J.; Li, X.; Zhao, Q.; Tade, Moses; Liu, Shaomin (Elsevier BV, 2017)
© 2017 Elsevier B.V. To achieve efficient conversion of solar to chemical energy in photocatalysis, development of visible-light-induced catalysts with high charge carrier mobility and superior activity is essential. In this work, a novel ß-Bi 2 O 3 /BiVO 4 nanocomposite with p-n heterojuction structure, which is assembled by interconnected quantum dots, has been successfully constructed through a facile approach. The structural and optical properties of the as-prepared materials were comparatively characterized. Steady-state and transient-state photoluminescence spectra demonstrate that the photo-induced charge carriers in ß-Bi 2 O 3 /BiVO 4 nanocomposite display higher separation and much longer lifetime than those in individual BiVO 4 samples, which is attributed to the formation of efficient interfacial electric field between ß-Bi 2 O 3 and BiVO 4 . The photocatalytic performance of the samples was explored by the degradation of ortho-dichlorobenzene (o-DCB). Electron spin resonance examinations confirmed that much more superoxide radicals were generated in the system of ß-Bi 2 O 3 /BiVO 4 nanocomposite, which could be mainly responsible for the outstanding activity. In addition, the adsorption and oxidation of o-DCB over the as-prepared materials were studied by in situ FTIR spectroscopy to investigate the nature of surface intermediates formed on the catalysts. To clarify charge migration route, a detailed photocatalytic mechanism in terms of the energy band structures is proposed.